Geohazard features of the Eastern Sardinia - Fabiano Gamberi; Michael Marani; Giacomo Dalla Valle; Marzia Rovere; Elisa Leidi; Alessandra Mercorella; Valentina Ferrante (Journal of Maps)
The MaGIC project (Marine Geohazard along the Italian Coasts) had the aim of mapping the geohazard in the Italian seas and resulted in numerous maps. In this paper, we present the maps: ‘Maps of Geohazard features of the eastern Sardinian Margin’. The Eastern Sardinia margin has mainly a narrow shelf, which reaches a width of 20 km only to the north. At the base-of-slope, a series of intra-slope basins sits in the structural depressions formed during the opening of the Tyrrhenian back-arc system. Submerged, coastal depositional bodies are present in the Olbia area where the continental shelf is large. They most likely represent the remnants of coastal environments formed during the last rise in sea level. They can represent important geo-resources for application in the issue of coastal erosion management. They are also the site of ecosystems hosting a specific biodiversity, which need to be preserved. In the central and southern part of the mapped area, the shelf is very narrow with an average width of about 4 km. Here, many canyon heads are very close to the coastline. They develop through retrogadational processes. Particularly in those canyons, where the canyon heads reach the coast, sediment instability represents an important source of geohazards to the coastal regions.